Climate responsive strategies versus the cultural and religioud dimensions in the architecture of Malay traditional house - Abdul majid, Noor hanita; Abdul Rahim, Zaiton; Denan, Zuraini (IIUM Press, 2011)
It is common knmvledge that the vernacular architecture of a place is a result of considerations on climatic, cultural and religious factors of the people; however, thorough analyses on the mentioned considerations have rarely been discussed. This article states in detail the multi-dimensional considerations in the architecture of the Malay traditional houses (MTH) that response to the climatic design strategies and the cultural and religious dimension in form of architectural elements. The discussions also focus on generic elements ofMTH in Peninsular Malaysia (irrelevant to their regions) with analysis on their response to the environment and vice-versa. The analyses indicate that the architectural elements incorporated in the design of the MTH are related to at least one of the mentioned considerations, i.e. culture, religion, climate. The fmdings are vital in sustaining the socio-cultural dimension in the provisions ofconducive public housing in Malaysia.